Implementing of Shalih Charity Program In Islamic Baroding School to Build Students' Entrepreneur Souls - Ratna, Chichi Dian; Syafi’i, Imam (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
The purpose of this study was to determine and describe 1) the application of the virtuous charity program at Islamic boarding schools in developing the entrepreneurial spirit of students, 2) the strategy of Islamic boarding schools in developing the entrepreneurial spirit of students, 3) the results of the righteous charity program in Islamic boarding schools in developing the entrepreneurial spirit of students living in at the Islamic boarding school Urwatul Wustho Bulurejo Diwek Jombang. This study uses a descriptive qualitative approach, namely by making observations in the field, with researchers as the main instrument to obtain data on how to plan, implement, and evaluate. In obtaining data related to the strategy of Islamic Boarding Schools in developing the entrepreneurial spirit of students, it was done by means of observation, interviews, and documentation. Then the data obtained were analyzed using data reduction, data presentation, and drawing conclusions. The results showed that the management of Islamic Boarding Schools in fostering the entrepreneurial spirit of students, namely: 1) Planning of Islamic Boarding Schools in fostering the entrepreneurial spirit of students, namely by synergizing between Islamic Boarding Schools, Schools, and Business Units, as for carrying out righteous charity programs, 2) Islamic Boarding School management strategies in fostering the entrepreneurial spirit of students is through Education and Training, 3) the physical results of the application of the righteous charity program can be used directly and the addition of increasing the ability of students in terms of knowledge and skills.